Ontology with human subjects testing: an empirical investigation of geographic categories. - Smith, Barry; Mark, David (American Journal of Economics & Sociology, 1999)
The paper presents a framework for the formulation and testing of ontological theories embodied in human cognition, concentrating primarily on the domain of geographic categories. Evidence for and against alternative theories of cognitive categories, for example on the part of E. Rosch and her associates, has been hitherto based primarily on studies of categorization of entities of table-top space (pets, tools, fruits). We hypothesize that the structure of our categories does not remain constant as we move from categories of objects at manipulable scales to geographic categories such as nation, mountain, river. More precisely: Geographic objects are not merely located in space, they are tied intrinsically to space in such a way that they inherit from space many of its structural (mereological, topological, geometrical) properties. Categorization in the geographic world is often size- or scale-dependent (consider: pond, lake, sea, ocean), and to a much greater extent than in the world of table-top space, the realization that a thing or type of thing exists at all in the geographic world may have individual or cultural variability. Geographic objects are in very many cases the products of delineation within a continuum, and the boundaries of such objects are themselves highly salient phenomena for purposes of categorization. A battery of experiments is described to test these hypotheses and to serve as a basis for more detailed ontological theorizing. Reprinted by permission of the publisher.